Analysis of the strain-rate sensitivity and the Bauschinger effect in fine-grained Cu and Cu-Ni alloys. (1st July 2017) - Shadkam, Ashkan
Abstract: The strain-rate sensitivity along the load-unload experiments on fine-grained pure Cu and Cu-Ni alloys are presented. For grain sizes lying in the range of 1–10 μm in pure Cu, Cu16at%Ni and Cu50at%Ni, an elevated rate sensitivity at the first few percent of plastic strain is observed. At this elasto-plastic transition, a substantial hysteresis during unloading is developed corroborating to the Bauschinger effect in the fine-grained materials. The strain rate sensitivity results are analyzed along the load-unload response of the materials. A dislocation-based phenomenological model is developed to describe the experimental observations. Graphical abstract: